Analysis of tofu‐related traits by a bench‐scale tofu production method and their relationship with agronomic traits in European soybean. (15th April 2018) - Kurasch, Alena K.; Hahn, Volker; Miersch, Martin; Bachteler, Kristina; Würschum, Tobias
Abstract: European tofu manufacturers are becoming more and more interested in locally grown soybeans. A prerequisite for the development of European tofu cultivars is to improve our understanding of how the environment and genetics affect soymilk and tofu quality, as well as how quality and agronomic traits are correlated. This study was based on 215 recombinant inbred lines derived from two populations and grown at three locations that were evaluated for tofu traits in a bench‐scale tofu laboratory. The heritabilities of most of the evaluated tofu traits were moderately high with h 2  > 0.6. We observed significant genotypic variance components, but an even stronger contribution of the location. The network analysis of the evaluated traits was population‐dependent; however, the tofu traits were not associated with any of the agronomic traits. Collectively, our results indicate the potential to improve tofu‐related traits in European soybean. The bench‐scale tofu production method provides a valuable tool to test soybean lines in breeding programmes; however, the method needs to be further improved and automated to minimize errors due to the laboratory staff.